IMPLEMENTASI KEBIJAKAN PENGANGKATAN SEKRETARIS DESA MENJADI PEGAWAI NEGERI SIPIL DI KECAMATAN DAMPAL SELATAN KABUPATEN TOLITOLI - Supiani, Supiani (Katalogis, 2014)
The policy implementation of the village secretaries as the civil servant aimed at creatingwell-order administrationof government and developmentas well as service, and effective people empowerment. The purpose of this study is to analyze and study the implementation of the village secretaries as the civil servants and to investigate the supporting and inhibit  factors of that policy which was studies based on the model of policy implementation of George C Edward III on the aspect of communication, resources, disposition and bureaucracry. This type of study was qualitative.  The  number  of  informant  was  12  persons  who  were  selected  by  using  purposive sampling technique. The result of study reveals that the policy implementationof the appointment of village secretaries as the civil servants had not yet been optimal as indicated by the following results: (1) Communication: there was no socialization from regional government about the policy of  regulation  of  PP  45  2007,  (2) the  resources  of  village  secretaries  did  not  fulfill  with  the requirement due to the old age and had no latest academic certificate possession. (3) the dispotion of  attitude and behavior  of  the implementor  in  the policy implementation  of  village sectetary appointment to be civil servant did not run well: some village had vacuum of village secretary position.(4) the bureaucracy structure of regional government in the policy implementation had worked  well  although  there  was  a  lack  coordination  in  the  appointment  of  village  secretary position. The inhibit factor of the policy implementation was lack of socialization from regional government about the policy and the policy and the regulation of PP 45 2007. The supporting factor  was  positive  responses  from  the  village  secretaries  for  their  appointment  as  the  civil servants.